73-2x=7x+22

Simple and best practice solution for 73-2x=7x+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 73-2x=7x+22 equation:


Simplifying
73 + -2x = 7x + 22

Reorder the terms:
73 + -2x = 22 + 7x

Solving
73 + -2x = 22 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
73 + -2x + -7x = 22 + 7x + -7x

Combine like terms: -2x + -7x = -9x
73 + -9x = 22 + 7x + -7x

Combine like terms: 7x + -7x = 0
73 + -9x = 22 + 0
73 + -9x = 22

Add '-73' to each side of the equation.
73 + -73 + -9x = 22 + -73

Combine like terms: 73 + -73 = 0
0 + -9x = 22 + -73
-9x = 22 + -73

Combine like terms: 22 + -73 = -51
-9x = -51

Divide each side by '-9'.
x = 5.666666667

Simplifying
x = 5.666666667

See similar equations:

| 85x-3x=8x+19 | | 22x-55=-22 | | 8n+6=78 | | (1-2x)*(x-3)=2 | | (N-8)*3=30 | | (N+4)*4=36 | | 2x+-8=-12 | | -12n-6(1-9n)=4(10n-5) | | -11(12+p)=-2p+8(p-8) | | 7-7x=155-35x | | 5y-(-2y)= | | 10n-27=63 | | (N-6)*10=20 | | 4-2.5= | | (N-6)*10=10 | | 68-4x=5x+17 | | -3y+2=-13 | | 59a+4=36 | | 3x+1=(x-9) | | (2x+3)(2x+5)(x-1)(x-2)=30 | | -10t-2=0 | | -10t^2-2t=0 | | 4x-(3x+7)=-1 | | 2x+3x-2=98 | | 5(4x-6)-8=6x-24 | | 2x^2+9*x-7=0 | | x-22=4 | | x+5+133+x= | | x^3+4x^2+5x+2=0 | | 3(5a-2)-2a+10= | | 3(n-1.8)=2n+1 | | 6(x-1)-2(2-x)=8-(2-6x) |

Equations solver categories